Historicizing psychedelics: counterculture, renaissance, and the neoliberal matrix - Sanchez Petrement, Mateo (Frontiers in Sociology, 2023)
In this essay, I would like to suggest that the historical transition of psychedelics from an association with counterculture to becoming part of the mainstream is related to the rise of what late cultural theorist Mark Fisher (2009) termed “capitalist realism” – the notion that there is no alternative form of social organization and, as such, capitalism simply is reality. For Fisher, the economic and political project of neoliberalism was the main agent behind this re-instauration of capitalist hegemony after its de-stabilization by the convergence of several radical forces at the end of the 1960s and early ‘70s, of which psychedelic “consciousness-expansion” was one. Thus, historicizing psychedelics within the shifts in political economy and culture associated with the “collective set and setting” of neoliberalism can serve both to understand the current shape and operations of the psychedelic “renaissance” as well as help us retrieve these substance’s lost political potential. Concretely, this essay argues that such potential was not inherent to psychedelics but embedded in the political economy of the New Deal order, which supported both the formation of discourses, demands, and hopes based on “the social” and, relatedly, the idea that “the personal is political”. As neoliberalism displaced this object of reference in favour of individualism, the personal was de-linked from the political and the dreams - and the threats - of psychedelic utopianism were successfully defused and forgotten. In the process, concretely, the anti-work and collective dimensions of the psychedelic counterculture have been all but lost as psychedelics have returned to enhance or treat individual brains - while leaving capitalist society unchallenged. In light of our ecological and social predicaments, the famous context-dependence of psychedelics can be a powerful reminder that, contra individualism, the social and political traverse the personal - and thus that to change the self in line with the psychedelic values of love and connection ultimately requires changing the world.